Social isolation profiles and conditional process analysis among postoperative enterostomy patients with colorectal cancer - Yuan Liao; Xuelan Liu; Xinyu Wu; Chun Li; Yu Li (BMC Psychology)
Abstract Purpose This study aimed to identify social isolation latent profiles and analyze the specific mechanisms in which social support, resilience, and posttraumatic growth associated social isolation from the perspective of positive psychology. Suggestions were offered to improve the mental health status of postoperative enterostomy patients with colorectal cancer. Methods This was a cross-sectional survey. From December 2022 to September 2023, convenience sampling was used to select 303 enterostomy patients from three hospitals in Guangzhou. A paper questionnaire was used to investigate their levels of social support, resilience, posttraumatic growth, and social isolation. T-test, ANOVA, Pearson Correlation Analysis, Latent Profile Analysis and Conditional Process Analysis were used to analyze the correlation between variables. Results (1) Education level, occupation, family monthly income per capita and times of changing enterostomy bag per week were significantly associated with social isolation. (2) Social isolation of patients included low alienation-fluctuation group (Class 1, 13.9%), medium group (Class 2, 64.0%), high alienation-low meaning group (Class 3, 22.1%). (3) Social isolation was negatively correlated with social support, resilience, and posttraumatic growth (P < 0.001). (4) Resilience played a mediating role in the association between social support and social isolation. (5) The second half path of the mediation model was moderated by posttraumatic growth. Conclusions Clinical staff, community personnel and family members should pay attention to the potential differences in social isolation experienced by patients. Suitable psychological strategies should be employed to enhance resilience, promote posttraumatic growth, for improving the patients’ mental health levels and help them return to society.